2018
DOI: 10.29121/granthaalayah.v6.i4.2018.1642
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Prevalence of Eating Disorder Among Nursing Students of Lalitpur, Nepal

Abstract: Background: Perceived socio cultural pressure to become thin has an important impact on eating disorder during adolescence, but less is known about knowledge and prevalence of eating disorders in Nepal. Adolescents face special problems that are less common during childhood. Several studies indicate that the prevalence of eating disorders has been increased among adolescents. Objectives: The aim of the study was to identify the level of knowledge, and prevalence of eating disorders (ED) among adolescents. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The COVID-19 pandemic has paved the ground for the adoption of digital learning (Dhawan, 2020), especially in emerging and less developed economies. During the shutdown of universities and schools because of the pandemic, e-learning tools were critical in assisting teachers in facilitating student learning (Subedi et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has paved the ground for the adoption of digital learning (Dhawan, 2020), especially in emerging and less developed economies. During the shutdown of universities and schools because of the pandemic, e-learning tools were critical in assisting teachers in facilitating student learning (Subedi et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that two-thirds of the total participants had an E-learning experience before the COVID-19 pandemic, which was in contrast with previous studies where more than two-third of the respondents never attended any online classes. [ 9 10 ] Mobile smartphones opted as the medium for online classes compared to laptops and tablets, as reported earlier in their study; participants preferred mobile devices for online learning. [ 8 11 ] Mobile devices are handy and easy to carry and access, which adds to the popularity of devices compared to other devices.…”
Section: Discussionmentioning
confidence: 78%
“…[ 42 ] Carlson[ 43 ] shows the implementation and continued use of mobile phone in evidence-based practice among the nursing graduates. Others three studies done by Al-Azawei,[ 44 ] Subedi et al .,[ 45 ] and Almaiah et al . [ 46 ] also support the findings of the study.…”
Section: Discussionmentioning
confidence: 99%